Potential inappropriate medications and drug–drug interactions in adverse drug reactions in the elderly: a retrospective study in a pharmacovigilance database - Jiang, Huaqiao; Lin, Yanhua; Ren, Weifang; Lu, Lina; Tan, Xiaofang; Lv, Xiaoqun; Zhang, Ning (Frontiers in Pharmacology, 2025)
IntroductionPotential inappropriate medications (PIMs) and potential drug–drug interactions (pDDIs) are important factors leading to adverse drug reactions (ADRs) in the elderly. This study aimed to evaluate the incidence and pattern of PIMs and pDDIs in the elderly based on a real-world pharmacovigilance database and identify the variables associated with them.MethodsThis retrospective study evaluated PIMs and pDDIs by updated Beers criteria and Lexi-Interact online, respectively, using ADRs reported for those aged ≥65 years submitted between 2011 and 2023 from a real-world database of a tertiary care teaching hospital. Correlation factors were investigated by binary and multiple logistic regression analyses.ResultsA total of 1,423 ADRs were included and involved 2,238 prescribed drugs; 54.11% of the total were men, and 23.47% were classified as serious. The most commonly implicated pharmacological group was antimicrobial agents. Aspirin and clopidogrel emerged as the drugs causing the majority of ADRs. PIMs were detected in 32.04% of all ADR reports. Aspirin and diclofenac were the most common active pharmaceutical ingredients involved, and gastrointestinal bleeding was the primary clinical manifestation of severe ADRs caused by PIMs or involved in PIM-related risk factors. Age, number of diagnosed diseases and prescribed drugs, ADR severity and preventability, hypertension, coronary heart disease, and arthritis were independent influencing factors of PIMs. Among 498 ADR reports with ≥2 prescribed drugs, 202 cases (14.20%) had pDDIs. Blood and hematopoietic organ and cardiovascular agents were the most commonly involved categories. The most frequent drug combinations in classes C, D, and X were aspirin–clopidogrel, aspirin–heparin, and potassium chloride–promethazine, respectively. The majority of pDDIs increased the risk of bleeding through pharmacodynamic mechanisms. The number of prescribed drugs and diagnosed diseases, ADR severity and preventability, stroke, diabetes, and coronary heart disease, along with PIM use, were independent predictors of pDDIs.ConclusionThe incidence of PIMs and pDDIs was found to be relatively high in the elderly, especially in the treatment of cardiovascular and cerebrovascular diseases and non-steroidal anti-inflammatory drugs (NSAIDs), and relevant factors have been identified. Healthcare institutions should reinforce the management of rational drug use in the elderly to mitigate the occurrence of PIMs and pDDIs, thereby enhancing medication safety.